Content and efficiency of the technique, aimed at formation of "working" and "dynamic position" of lower acrobates, taking into account the requirements of the chosen specialty - Vladyslava Denysenko; Yuliya Maksymova; Mikhail Filippov (Kazimierz Wielki University, 2020)
The content of the methodology aimed at the formation of "working" and "dynamic posture" of bottom acrobats who train at the stage of preliminary basic training is discussed in the article presented. The methodology mentioned was developed with taking into account the requirements of the athletes' chosen specialty, as well as on the basis of the kinematic structure of motor action which form the basis of functional duties of the bottom acrobat. It solved the following tasks: formation of a "working posture", formation of "rational dynamic posture" of a bottom acrobat in the performance of functional duties; optimization of balancing technique and throwing actions of the bottom acrobats. The sequential implementation of the following stages created the algorithm of the methodology developed. It included formation of a "working posture" under simple conditions; formation of a "working posture" under the conditions of an increased load on the muscles that fix the "working posture"; formation of the "working posture" under the various spatio-temporal conditions; formation of a "rational dynamic posture" under simple conditions; formation of "rational dynamic posture" under conditions with a reduced  support area; formation of "working posture" and "rational dynamic posture" under the conditions close to the performance of acrobatic exercises. AS a result of the experiment the Authors has shown that the use of the technique developed contributes to the optimization of the balancing technique and technique of throwing actions of the bottom acrobats. So among main group acrobats the indicators of "working posture" and "dynamic posture" significantly differ (p<0.05) from those in control group and approach the model characteristics.